Post-coronavirus disease 2019 polyneuropathy with significant response to immunoglobulin therapy: a case report - A. Saleh (BMC, 2021)
Abstract Background The symptoms of coronavirus disease 2019, caused by the novel severe acute respiratory syndrome coronavirus 2, were originally assumed to be mainly respiratory. With increasing knowledge, however, it turned out that the spectrum of complaints varies broadly with age and concomitant diseases. While many neurological symptoms were reported in the context of the disease, ranging from permanent fatigue to recurrent headaches and concentration disturbance, treatment approaches are still in development. This case discusses a possible treatment approach with immunoglobulin therapy and its outcomes. Case presentation We present the case of a 56-year-old Caucasian female patient who, following coronavirus disease 2019, developed peripheral sensory and autonomic disturbances that fell within subacute demyelinating neuropathy. Because a significant improvement in symptoms as well as in the results of clinical and electrophysiological examination was reported after immunoglobulin therapy, long-term therapy does not appear to be necessary. Conclusion Given the significant subjective and objective improvement reported, this case provides additional evidence that immunoglobulin therapy can be considered in post-coronavirus disease 2019 syndrome.